Medication guide for the perioperative management of oral antineoplastic agents in cancer patients. Issue 1 (2nd January 2022) - Villanueva-Bueno, Cristina; Escudero-Vilaplana, Vicente; Collado-Borrell, Roberto; Giménez-Manzorro, Álvaro; Ribed, Almudena; Marzal-Alfaro, Belén; Revuelta-Herrero, José Luis; Gonzalez-Haba, Eva; Herranz, Ana; Sanjurjo, Maria
ABSTRACT: Background: Oral antineoplastic agents (OAAs) are high-risk drugs that may increase the risk of bleeding, difficulty in wound healing, or produce alterations in coagulation and/or platelet aggregation. These aspects had to be highly considered throughout the entire perioperative process. Our aim was to create a comprehensive management medication guide based on reconciliation and dose adjustment recommendations for OAAs in patients undergoing a surgical intervention. Research design and methods: We analyzed all OAAs approved by the EMA in November 2020. We assessed data related to dose adjustment, drug reconciliation, coagulation disturbances, or anticoagulant interactions from the FDA and EMA summary of product characteristics. Results: We analyzed 67 OAAs. We identified that 51 (76.2%) OAAs can produce alteration in the platelet count, 12 (17.9%) affect the wound healing and recovery process, and 32 (47.8%) require control and monitoring in case of combination with anticoagulants. Only 13 (19.4%) OAAs, most of them antiangiogenics, have specific recommendations for temporary suspension before surgery. Conclusions: Most OAAs require perioperative monitoring. This review can serve as an easy (simple, effective) tool to help healthcare professionals involved in patient care to manage OAAs during the perioperative process.